PM.32 Platelet Function is Significantly Reduced in the First Trimester of Pregnancy Compared to the Non-Pregnant State. (26th April 2013) - Burke, N; Flood, K; Murray, A; Dempsey, M; Dicker, P; Geary, M; Kenny, D; Malone, F
Abstract : Abnormalities of platelet function have been implicated in a number of obstetric complications and anti platelet therapy is used to prevent certain conditions. Research of platelet function in pregnancy has yielded conflicting results. We sought to critically evaluate platelet reactivity in pregnancy using an assay which allowed several agonists of varying concentrations to be assessed concurrently and aimed to clarify platelet reactivity in normal pregnancy. A prospective longitudinal study was performed throughout uncomplicated singleton pregnancies with patients recruited prior to 15 weeks' gestation. They were controlled for a number of factors known to affect platelet reactivity. Blood samples were obtained in each trimester (n = 36). Thirty non-pregnant healthy female volunteers also had a platelet assay performed. A modification of standard light transmission aggregometry was used to assess platelet reactivity, with light absorbance measured following addition of 5 different agonists at sub-maximal concentrations. Dose-response curves were plotted and the Ec50 was calculated for each agonist. Platelet reactivity, as demonstrated by the Ec50, was significantly reduced in the 1 st and 2 nd trimester of pregnancy compared to the non pregnant state particularly with respect to collagen, (p = 0.002). Within the pregnancy cohort the platelet reactivity increased as the pregnancy progressed, most evident in response to arachidonic acid (AA) (p = 0.033). This study demonstrates that platelet reactivity is altered in pregnancy, highlighted by the significant reduction in reactivity seen in the 1 st trimester. This information will be critically important for designing and interpreting interventions to prevent obstetric complications, such as preeclampsia.